Indexing Abu Muhammad Ibn Khazraj. / Indexación de Abu Muhammad Ibn Khazraj. - AHMED BANI YASSIN, YOUSSEF; HADI NAYEF AL-QAIDA, ABDUL (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The literature on the Sheikhs’ biographies section is one of the most important categories in the writings about the science of narrators. Historical writing in Andalusia is known for considering this category since its early history to such an extent that it is almost true to say that every scholar wrote a dictionary on his sheikhs and audiences, but unfortunately, most of these indexes were lost and given little attention by modern scholars.Two themes structure the research topic, the first aims to introduce the author, his birth, life and works, while the second introduces the book, its subject matter, its methodology and its limits. RESUMEN La literatura sobre la sección de biografías de los jeques es una de las categorías más importantes en los escritos sobre la ciencia de los narradores. La escritura histórica en Andalucía es conocida por considerar esta categoría desde su historia temprana hasta tal punto que es casi cierto decir que cada estudioso escribía un diccionario sobre sus jeques y audiencias, pero desafortunadamente, la mayoría de estos índices se perdieron y se les prestó poca atención por estudiosos modernos. Dos temas estructuran el tema de investigación, el primero tiene como objetivo presentar al autor, su nacimiento, vida y obras, mientras que el segundo presenta el libro, su tema, su metodología y sus límites.